2005
DOI: 10.1038/modpathol.3800252
|View full text |Cite
|
Sign up to set email alerts
|

Mutational activation of BRAF is not a major event in sporadic childhood papillary thyroid carcinoma

Abstract: Papillary thyroid carcinoma may encompass a mixed group of neoplasms where divergence in clinical behavior may reflect distinct genetic alterations. For example, young patients with papillary thyroid carcinoma have a better prognosis than affected adults, and their carcinomas are much more likely to harbor chromosomal rearrangements involving the RET proto-oncogene. Mutational activation of the BRAF oncogene has recently been identified as the most common genetic alteration in papillary thyroid carcinoma, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
43
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 18 publications
5
43
0
1
Order By: Relevance
“…36 A point mutation in codon 600 of BRAF is the most prevalent mutation in adult papillary thyroid carcinoma; however, in childhood patients this mutation is very uncommon. [37][38][39][40][41][42] Of note is that in the youngest patients with papillary carcinoma, mutant BRAF is virtually absent whereas in older children and adolescents the frequency of mutant BRAF rises with increasing age. The BRAF protein is an effector of the MAP-kinase pathway; its impairment through missense mutation leads to increased cellular proliferation, dedifferentiation and genomic instability (reviewed by Xing 43 ).…”
Section: Point Mutationsmentioning
confidence: 96%
“…36 A point mutation in codon 600 of BRAF is the most prevalent mutation in adult papillary thyroid carcinoma; however, in childhood patients this mutation is very uncommon. [37][38][39][40][41][42] Of note is that in the youngest patients with papillary carcinoma, mutant BRAF is virtually absent whereas in older children and adolescents the frequency of mutant BRAF rises with increasing age. The BRAF protein is an effector of the MAP-kinase pathway; its impairment through missense mutation leads to increased cellular proliferation, dedifferentiation and genomic instability (reviewed by Xing 43 ).…”
Section: Point Mutationsmentioning
confidence: 96%
“…In an orthotopic mouse model for papillary thyroid carcinoma (PTC), sorafenib dramatically reduced tumor growth in PTC with RET/PTC1 mutation to a greater extent than in PTC with BRAF mutation [20]. This was compelling since children with PTC are more likely to have RET/PTC rearrangements and less likely to harbor somatic BRAF mutations [21,22]. …”
Section: Introductionmentioning
confidence: 99%
“…Further studies focused on searching the relationship between the mutation and other features of an unfavorable course of the disease (22)(23)(24)(25)(26)(27)(28)(29)(30)(31). As early as in 2003 Nikiforova et al (23) paid attention to the relationship between BRAF mutation and advanced age of patients and also histological subtypes of cancer (classic and tall cell PTC, extracapsular extension and a frequent incidence in patients in III and IV stages.…”
Section: The Relationship Of Braf Mutation With Other Clinico-patholomentioning
confidence: 99%
“…Other observations were noted in the following years. A number of studies from single centers were reported, which analyzed the prevalence of the mutation and its relationship with other clinicopathological risk factors (24)(25)(26)(27)(28)(29)(30)(31)(32)(33). However, the studies resulted in different, often conflicting results, which were related to differences in methodology, i.e., group selection, group size, time of the follow-up and the type of statistical analyses (uni-and/or multi-variable), the differences in BRAF mutation occurrence in different populations, the methodology of BRAF identification and also lack of the results of validations.…”
Section: The Relationship Of Braf Mutation With Other Clinico-patholomentioning
confidence: 99%